2017
DOI: 10.1371/journal.pone.0173601
|View full text |Cite
|
Sign up to set email alerts
|

Problems identified by dual sensory impaired older adults in long-term care when using a self-management program: A qualitative study

Abstract: ObjectiveTo gain insights into the problems of dual sensory impaired older adults in long-term care. Insights into these problems are essential for developing adequate policies which address the needs of the increasing population of dual sensory impaired older adults in long-term care.MethodsA qualitative study was conducted in parallel with a cluster randomized controlled trial. Dual sensory impaired older adults in the intervention group (n = 47, age range 82–98) were invited by a familiar nurse to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Overall, treatment delivery was fair. When compared with the findings of the parallel study analysing the problems addressed with the SMP-DSI, 45 we observed differences in treatment delivery: problems in controlling personal space were addressed to a greater extent than were the problems requiring behavioural involvement of others. Of the problems in controlling personal space, 27 of the 44 (61.3%) were fully addressed using all five SMP-DSI steps.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Overall, treatment delivery was fair. When compared with the findings of the parallel study analysing the problems addressed with the SMP-DSI, 45 we observed differences in treatment delivery: problems in controlling personal space were addressed to a greater extent than were the problems requiring behavioural involvement of others. Of the problems in controlling personal space, 27 of the 44 (61.3%) were fully addressed using all five SMP-DSI steps.…”
Section: Discussionmentioning
confidence: 81%
“… 44 In addition, we analysed the collection of problems addressed with the SMP-DSI in this cRCT; these were reported in a second separate qualitative study. 45 …”
Section: Methodsmentioning
confidence: 99%
“…Caregivers can counteract this feeling of incoherence over time through a combination of emotional and practical support (Olesen and Jansbøl, 2005). Roets-Merken et al (2017) describe a category of existential challenges when becoming deafblind, implying thoughts like being stupid, forgotten, and not being significant anymore. As well, to orientate oneself is one of the most affected abilities when becoming deafblind.…”
Section: Discussionmentioning
confidence: 99%
“…The need for existential care appears explicitly in older age because of prevalent physical and mental decline and the awareness of the increasing likelihood to die (McFadden, 2013). A life with deafblindness is often accompanied by identity crises, implying an existential feeling of loneliness (Gullacksen et al, 2011), disconnection from others (Roets-Merken et al, 2017), and the world (Prause et al, in press), as well as questions about one's value (Johansson, 2017). Therefore, access to existential care appears to be an essential concern for older persons with acquired deafblindness.…”
Section: Introductionmentioning
confidence: 99%
“…As individuals age, there is not only increased risk of vision loss and cognitive decline, but there are often additional declines in other sensory functions, including hearing [11,[44][45][46][47]. The studies reported within this scoping review primarily focused on visual impairment, but it is likely that a large number of the participants in the reviewed studies also experienced age-related hearing loss.…”
Section: Limitations and Identified Priorities For Future Directionsmentioning
confidence: 99%